Internal challenges of adoption of e-procurement in higher education institutions in Uganda: A case of Makerere University. - Watuleke, Joseph (IJRDO- Journal of Educational Research, 2017)
E-procurement has been widely recognized for carrying the potential to significantly increase the buyers’ and sellers’ benefits. The Deutsche Bank research (Meyer, 2011) established that a full transition to e-procurement could generate savings of between 50 billion and 70 billion Euro. Earlier research had shown that the extent of e-procurement infrastructure integration between organizations had a direct impact on the savings and benefits obtained by an organization (Min and Galle, 2003). Implying that lack of or poor integration of e-procurement infrastructure lowered benefits and could increase costs, while a good integration had yielded the opposite effect. As a result of this promise, business today has focused on the supply function to a greater extent than it previously did (Purchase & Dooley, 2005). E-procurement which has been offered varied interpretations simply refers to the process of purchasing goods and services electronically required for an organization’s operation (Mitchell, 2000). It involves electronic interaction between or among parties involved in the procurement process rather than physical exchange or contact. While there are an array of opportunities and advantages e-procurement offers, adoption of e-procurement systems in organizations especially Higher education institutions is not happening as quickly as predicted. User organizations are faced with a complex decision to make as to whether along to digitalize their purchases and procurement function or remain traditional (Davila, Gupta & Palmer, 2003). Some reasons have been presented by researchers to explain the delayed adoption of e-procurement by many of organizations. While some organizations have opted to adopt a ‘wait and see’ approach to eprocurement, others are faced with a complexity of decision resulting from an array of software programs available on market (Osmonbekov, Bello and Gilliland, 2002).